Psychological practices and palliative care in the pandemic context: a study of social representations (Research, Society and Development, 2022)
Palliative care is characterized as assistance performed by a multidisciplinary team with the purpose of providing an improvement in the quality of life of patients and their families in the face of a life-threatening disease. In this sense, the objective was to understand the social representations about palliative care within the competence of hospital psychologists during the Covid-19 pandemic. Sixteen hospital psychologists, aged between 23 and 60 years (M = 36.56; SD = 11.89), participated in the study, most of them female, who answered a sociodemographic questionnaire and a semi-structured interview. Data were processed by the SPSS and IRAMUTEQ software and impediment through descriptive statistics, lexical analysis, and word cloud. The results showed that knowledge about palliative care was anchored in the theoretical and practical knowledge involved by implicative aspects in the pandemic context. Thus, it is expected that this work will contribute with new knowledge that will improve the practice of hospital psychologists.